Advocates and Law Enforcement Officers: Towards Harmonization in the Legal Enforcement Process: Advokat dan Aparat Penegak Hukum: Menuju Harmonisasi dalam Proses Penegakan Hukum - Zamroni, Mohammad; Noor, M. Tauchid (Perspektif Hukum, 2025)
The Advocates are the only law enforcers who can be involved in all law enforcement processes. Advocates can also intersect and conflict with all other law enforcers in the law enforcement process. Therefore, harmonization of advocates with other law enforcers in the law enforcement process is essential. This study aims to determine the urgency of such harmonization and the factors that influence it. This research is a normative juridical research using a statutory and conceptual approach. Primary and secondary legal materials were collected through literature study and analyzed qualitatively. This research found that harmonizing advocates and other law enforcers in the law enforcement process is essential because without harmonization, the law enforcement process cannot run well, thus harming the interests of the people involved in the case. Three factors influence the harmonization of advocates with other law enforcers in the law enforcement process: statutory, authority, and interest factors.